2004
DOI: 10.1002/ijc.20628
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of SYK expression by inhibition of DNA methylation suppresses breast cancer cell invasiveness

Abstract: The gene product of spleen tyrosine kinase (SYK) has been implicated in the suppression of breast cancer invasion. We previously reported that SYK expression is lost in a subset of breast cancer; primarily by methylation-mediated gene silencing. In our study, we explored the possibility of using a DNA methyltransferase inhibitor, 5-aza-2 -deoxycytidine (AZA), to suppress breast cancer cell invasion by restoring SYK expression. We found that AZA treatment reestablished the expression of SYK(L) that was accompan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
46
0
21

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 35 publications
5
46
0
21
Order By: Relevance
“…33 Moreover, it was demonstrated that loss of Syk expression in breast cancer and T-cell acute lymphoblastic leukemia cells occurs at the transcriptional level, and is a result of DNA hypermethylation. 31,36,37 Treatment of these cells with 5-azacytidine (5-aza), a methylation inhibitor, restored Syk expression and function. 36,37 5-Aza is a nonspecific Syk DNA methyltransferase inhibitor that is used for the treatment of myelodysplasia 38 and possibly AML.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Moreover, it was demonstrated that loss of Syk expression in breast cancer and T-cell acute lymphoblastic leukemia cells occurs at the transcriptional level, and is a result of DNA hypermethylation. 31,36,37 Treatment of these cells with 5-azacytidine (5-aza), a methylation inhibitor, restored Syk expression and function. 36,37 5-Aza is a nonspecific Syk DNA methyltransferase inhibitor that is used for the treatment of myelodysplasia 38 and possibly AML.…”
Section: Introductionmentioning
confidence: 99%
“…31,36,37 Treatment of these cells with 5-azacytidine (5-aza), a methylation inhibitor, restored Syk expression and function. 36,37 5-Aza is a nonspecific Syk DNA methyltransferase inhibitor that is used for the treatment of myelodysplasia 38 and possibly AML. 39,40 However, the effects of 5-aza on leukemia cell growth are not well defined.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant promoter methylation of CpG-rich areas of promoter regions (along with the related epigenetic phenomenon of histone deacetylation) is the most frequent mechanism of tumor suppressor gene silencing in human tumors (Jones and Baylin, 2002). Three genes that regulate cytokine signaling, SHP1 (12p13-22), SOCS1 (16p12-13) and SYK (9q22), are inactivated through hypermethylation of their promoters in certain tumor types (Yoshikawa et al, 2001;Yuan et al, 2001;Oka et al, 2002). These genes are frequently methylated in lymphomas and leukemias (SHP1) (Oka et al, 2002;Chim et al, 2004), MMs (SOCS1) (Chim et al, 2004;Galm et al, 2003) and Tcell leukemias (SYK) (Goodman et al, 2003).…”
mentioning
confidence: 99%
“…Methylated cell lines were cultured with Figure 1 Methylation-specific PCR (MSP) assay, RT-PCR for SHP1, SOCS1 and SYK and Western blot analyses for SHP1 and SYK in lymphoma (ly) leukemia (le) and MM cell lines. Aberrant promoter methylation of SHP1, SOCS1 and SYK was determined on bisulfite-treated DNA by the method of MSP (Herman et al, 1996), using primers for methylated sequences and methodologies previously described for SHP1 (Oka et al, 2002), SOCS1 (Galm et al, 2003) and SYK (Yuan et al, 2001). MSP assays can detect the presence of one methylated allele in the presence of 10 3 -10 4 unmethylated alleles.…”
mentioning
confidence: 99%
See 1 more Smart Citation